2020
DOI: 10.1161/strokeaha.120.031144
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Triage Strategies for the Transportation of Suspected Stroke Patients in the United States

Abstract: Background and Purpose: Ischemic stroke patients with large vessel occlusion (LVO) could benefit from direct transportation to an intervention center for endovascular treatment, but non-LVO patients need rapid IV thrombolysis in the nearest center. Our aim was to evaluate prehospital triage strategies for suspected stroke patients in the United States. Methods: We used a decision tree model and geographic information system to estimate outcome of suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…The restrictions on traffic might be an important factor that patients who lived in villages and towns around Wenzhou could arrive at the hospital formerly [ 13 ]. The restrictions increased the time for patients to arrive at a district medical center so that patients and their relatives were more likely to go to their local hospital [ 14 ]. Another reason was that more patients exceeding the treatment time window which decreased the number of patients who received treatment successfully.…”
Section: Discussionmentioning
confidence: 99%
“…The restrictions on traffic might be an important factor that patients who lived in villages and towns around Wenzhou could arrive at the hospital formerly [ 13 ]. The restrictions increased the time for patients to arrive at a district medical center so that patients and their relatives were more likely to go to their local hospital [ 14 ]. Another reason was that more patients exceeding the treatment time window which decreased the number of patients who received treatment successfully.…”
Section: Discussionmentioning
confidence: 99%
“…This is not as daunting as it may seem. Multiple modeling studies have found that LVO triage may not result in overwhelmed stroke centers or missed thrombolysis opportunities [13,30,36,41]. If sensitivity is prioritized, CPSS ≥ 2 would be a strong and easy stroke severity tool choice because it performs just as well as other tools at their sensitive score cutpoints (86% sensitivity and 61% specificity) and would require little to no additional EMS training [25].…”
Section: Prehospital Stroke Severity Toolsmentioning
confidence: 99%
“…(82)(83)(84) Similar to the evolution of STEMI care over time, the care of LVO stroke is transitioning from the current "drip and ship" strategy to an approach in which the ground EMS team providing 9-1-1 response considers bypass of local hospitals that lack interventional therapies in favor of direct transport to primary and comprehensive stroke centers capable of performing endovascular therapies, even if transport time is extended 60 minutes or more. (85,86) A recent evaluation of seven different LVO prediction algorithms in use in the EMS setting showed wide variability in sensitivity (38-62%) and specificity (80-93%), high negative predictive values (95-96%), but poor positive predictive values (21-32%), with no specific algorithm outperforming the others across all of the measures of predictive value that the study evaluated. (87) Further, the best performing algorithm (RACE, PPV 32%) unfortunately also had the lowest prehospital feasibility score (78%).…”
Section: Neurologic Emergenciesmentioning
confidence: 97%